Analisis Pengaruh Intellectual Capital Terhadap Financial Performance dengan Competitive Advantage Sebagai Variabel Intervening - Muzakar Isa; Della Ariska Deviana (Benefit: Jurnal Manajemen dan Bisnis, 2018)
Abstract : The purpose of this research are to analyze: (1) influence of intellectual capital to the competitive advantage; (2) influence of intellectual capital to the financial performance; (3) the mediating effect of competitive advantage in the relationship between intellectual capital and financial performance. The technique of the sample collection was purposive sampling and based on the determined criteria, so 21 companies which have met the criteria have been selected as samples. This research was casual comparative. The analysis used in this study includes classical assumption test, liniar regression analysis and path analysis. The result of this research show that: (1) Intellectual Capital has a significant and positive effect on Competitve Advantage; (2) Intellectual Capital significantly and positively influence on Financial Performance; (3) Competitive Advantage variabel is mediated Intellectual Capital to the Financial Performance. Keyword: Intellectual Capital, Financial Performance, Competitive AdvantageAbstraksi : Penelitian ini bertujuan untuk menganalisis: (1) pengaruh intellectual capital terhadap competitive advantage; (2) pengaruh intellectual capital terhadap financial performance; (3) pengaruh mediasi hubungan antara intellectual capital dan financial performance. Teknik pengambilan sampel adalah purposive sampling dan berdasarkan kriteria yang ditentukan, sehingga diperoleh 21 perusahaan yang memenuhi kriteria. Penelitian ini termasuk kausal komparatif. Analisis yang digunakan dalam penelitian ini meliputi uji asumsi klasik, analisis regresi linier dan analisis jalur. Hasil penelitian ini menunjukkan bahwa: (1) Intellectual Capital mempunyai pengaruh positif dan signifikan terhadap Competitive Advantage; (2) Intellectual Capital mempunyai pengaruh positif dan signifikan terhadap financial performance; (3) Competitive Advantage memediasi Intellectual Capital terhadap Financial Performance. Abstract